The Influence of Health Spending and Political Affiliation on Stunting Prevalence In Indonesia: A Dynamic Panel Analysis (2015-2022) - Lestari Lestari; Heni Wahyuni; Wisnu Setiadi Nugroho (Journal of Developing Economies, 2026)
Objective: This study evaluates the impact of health function spending and political affiliation on stunting reduction in Indonesia from 2015 to 2022. Design/Methods: Using the Grossman health production function model to examine how socioeconomic, demographic, environmental, and food adequacy factors influence stunting prevalence among children under five. A dynamic panel analysis via the Generalized Method of Moments (GMM) is employed to address potential endogeneity. Findings: The results show that quantifying health function spending as the ratio of spending realization to total regional budget (APBD) does not significantly impact the reduction of stunting prevalence across all provinces, but becomes impactful when measured per capita. In this case, health function spending significantly reduces the prevalence of stunting. Additionally, political affiliation plays a crucial role. Regions governed by leaders affiliated with the central government tend to demonstrate greater success in reducing stunting. Originality/Value: This study introduces a political dimension to examining the health production function by interpreting political affiliation as a factor mediating the relationship between health function spending and stunting prevalence. Practical/Policy implication: These findings suggest that to enhance the effectiveness of health spending, policymakers should prioritize per capita allocations and ensure that funds are directed toward regions and populations most in need. Additionally, efforts should be made to mitigate the influence of political competition on health budget allocation, ensuring that resources are distributed based on need rather than political affiliation